Pengembangan Media Pembelajaran Interaktif Berbasis Educaplay pada Mata Pelajaran Informatika di SMP Negeri 1 Ciwaru - Fuadi, Wafa; Nurjanah, Hifni Fitriah (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to develop interactive learning media based on Educaplay in class VII Informatics subjects at SMP Negeri 1 Ciwaru. The background of this research is based on the low motivation of students in learning Informatics which is still dominated by the lecture method, and not optimal utilization of technology-based learning media. This research uses the development research method (Research and Development) with the ADDIE model. The subjects of this study were 30 seventh grade students. Data collection was done through observation, interviews, and questionnaires. Product validation was conducted by material experts and media experts. The results of the material expert validation showed a feasibility percentage of 92% (very feasible category), while the media expert validation obtained a percentage of 86% (very feasible category). Product trials were conducted through beta test 1 (small group) and beta test 2 (large group). The results of beta test 1 obtained a percentage of 75% (decent category), and beta test 2 obtained a percentage of 88% (very decent category). Based on the results of validation and trials, Educaplay-based interactive learning media is declared feasible for use as an alternative learning media that can increase student involvement and motivation in learning Informatics. This media can provide a more enjoyable, contextual, and interactive learning experience.